Skin Resident Memory T Cells May Play Critical Role in Delayed-Type Drug Hypersensitivity Reactions - Schunkert, Elisa Maria; Shah, Pranali Nitin; Divito, Sherrie Jill (Frontiers in Immunology, 2021)
Delayed-type drug hypersensitivity reactions (dtDHR) are immune-mediated reactions with skin and visceral manifestations ranging from mild to severe. Clinical care is negatively impacted by a limited understanding of disease pathogenesis. Though T cells are believed to orchestrate disease, the type of T cell and the location and mechanism of T cell activation remain unknown. Resident memory T cells (TRM) are a unique T cell population potentially well situated to act as key mediators in disease pathogenesis, but significant obstacles to defining, identifying, and testing TRM in dtDHR preclude definitive conclusions at this time. Deeper mechanistic interrogation to address these unanswered questions is necessary, as involvement of TRM in disease has significant implications for prediction, diagnosis, and treatment of disease.